Development of Low-Fat Functional Pork Nuggets with Incorporation of Whey Protein Concentrate : 10.5958/2581-6616.2020.00006.7 - Jangir, Apeksha; Malav, Om Prakash; Chatli, Manish K.; Mehta, Nitin; Wagh , Rajesh V. (Journal of Meat Science, 2021)
Three different levels of whey protein concentrate viz. 3%, 5% and 7% were incorporated as fat replacers in pork nuggets after replacing  the fat in the prestandardized formulation of pork nuggets and were compared with high fat control with 10% added fat. The control  and treatment products were analysed for physicochemical parameters, proximate composition, instrumental colour profile, texture pro file analysis and sensory evaluation. The pH of the treated pork nuggets incorporated with whey protein concentrate was significantly  (P
Keywords: Cooking yield; texture; low fat; instrumental colour profile